Glyphosate, Phorate, and Monocrotophos Hazardous Pesticide Usage and Its Public Health Impact – An Empirical Analysis - Elakiya Sugumaran; Prashanthy.M.R; Bharathwaj; Prabu.D; Sunayana Manipal; Rajmohan; Vishali.M (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Pesticides are used extensively around the world and it has many health significance due to the usage of glyphosate,phorates, and monocrotophos that were mainly used as organophosphate pesticides in all the countries. Aim: To evaluate the countries which banned glyphosate, phorates, and monocrotophos hazardous pesticide usage and to assess the severity of risks caused by exposure of the pesticides.Methodology: This study was based on a review of scientific publications on usage of hazardous pesticides such as glyphosate, phorates, monocrotophos, and its impact on public health.Data were retrieved from the manual and electronic database by using the search engines (PubMed and google scholar). Results: European countries had banned glyphosate, phorate, and Monocrotophos pesticides within the year 2015 to 2019 whereas in India, two states namely Punjab and Kerala had banned glyphosate pesticides by the year 2018 to 2019, Phorates pesticides had banned in 2019, and monocrotophos pesticides were banned by the two states namely Punjab and Maharashtra in the year 2018. Glyphosate pesticides caused more impact on cancer and other health effects in the body in contrast to the other two pesticides had a lesser impact on cancer.Conclusion: Chemical pesticides can protect and improve farm productivity. However, their inimical and environmental health effects makes an inadequate long-term solution. Hence, to overcome this problem, there must be minimization of the usage of chemical pesticides and introduction of eco-friendly natural pesticides, which are easily accessible, low cost, and healthy method of a pest control system.